Flora of Bahia: Surianaceae - Silva, Diego Nunes da (SITIENTIBUS série Ciências Biológicas, 2020)
The floristic survey of Surianaceae from Bahia, Brazil, is presented. Only the monospecific genus Suriana was found in the state. Descriptions are presented for the family, genus and species, as well as general comments, field photos and a geographic distribution map for Suriana maritima in the state.